2013
DOI: 10.1371/journal.pone.0066372
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplasma-Responsive microRNAs Modulate Hormonal, Nutritional, and Stress Signalling Pathways in Mexican Lime Trees

Abstract: BackgroundWitches’ broom disease of Mexican lime (Citrus aurantifolia L.), which is associated to the phytoplasma ‘Candidatus Phytoplasma aurantifolia’, is a devastating disease that results in significant economic losses. Plants adapt to biotic stresses by regulating gene expression at the transcriptional and post-transcriptional levels. MicroRNAs (miRNAs) are a recently identified family of molecules that regulate plant responses to environmental stresses through post-transcriptional gene silencing.MethodsUs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 51 publications
4
47
1
Order By: Relevance
“…Thence, we compared the common DEMs in the three paulownia species with the DEMs detected in our previous studies [23,[51][52][53][54], and found that miR156, miR398, miR408, and miR2118 were common DEMs in the healthy vs. phytoplasma-infected seedling comparisons. Thirdly, to confirm the key miRNAs related to witches' broom, we compared the four identified miRNAs with the miRNAs detected in phytoplasma-infected Mexican lime, Ziziphus jujuba, and mulberry [7, [14][15][16], and found that miR156 was the only common miRNA among the phytoplasma-responsive miRNAs in all these studies. We then analyzed the expression of miR156 in the three paulownia species and compared the expression level of miR156 of other phytoplasma-infected plants, and found their expression levels in most of the above plants were up-regulated in the phytoplasma-infected plants.…”
Section: Mir156 Is the Key Regulatory Factor Related To Witches' Broommentioning
confidence: 99%
See 2 more Smart Citations
“…Thence, we compared the common DEMs in the three paulownia species with the DEMs detected in our previous studies [23,[51][52][53][54], and found that miR156, miR398, miR408, and miR2118 were common DEMs in the healthy vs. phytoplasma-infected seedling comparisons. Thirdly, to confirm the key miRNAs related to witches' broom, we compared the four identified miRNAs with the miRNAs detected in phytoplasma-infected Mexican lime, Ziziphus jujuba, and mulberry [7, [14][15][16], and found that miR156 was the only common miRNA among the phytoplasma-responsive miRNAs in all these studies. We then analyzed the expression of miR156 in the three paulownia species and compared the expression level of miR156 of other phytoplasma-infected plants, and found their expression levels in most of the above plants were up-regulated in the phytoplasma-infected plants.…”
Section: Mir156 Is the Key Regulatory Factor Related To Witches' Broommentioning
confidence: 99%
“…The discovery of miRNAs as gene regulators has broadened the perspectives of the mechanisms involved in gene regulation, and revealed that miRNAs are associated with many biological processes such as plant development, protein degradation, cell proliferation and differentiation, and signal transduction, and play important roles in resistance to abiotic and biotic stresses [12,13]. A number of studies of plant-phytoplasma interactions have shown that miRNAs are involved in gene regulation in many plants, including Mexican lime, Mulberry, Catharanthus roseus, Peanuts, and Ziziphus jujube [14][15][16]. Some miRNA families are conserved among various plants; however, changes in their expression patterns in response to different phytoplasma infections were different in different plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5’-RLM-RACE experiments were carried out using the modified RNA ligase-mediated rapid amplification of 5’ cDNAs method as described [28,29], PCRs were carried out on mRNA isolated from Z . jujuba infected with witches’-broom disease using the GeneRacer 5’ primer and the nesting gene-specific primers (S2 Table).…”
Section: Methodsmentioning
confidence: 99%
“…P. aurantifolia" Zamharir et al, 2011). Ehya et al (2013) detected miRNA families that are expressed differently upon infection with phytoplasma species. Most of the miRNAs had variants with small sequence variations (isomiRs), which are expressed differently in response to pathogen infection.…”
Section: Introductionmentioning
confidence: 99%